"We are All Refugees": Camps and Informal Settlements as Converging Spaces of Global Displacements. (26th May 2020) - Huq, Efadul; Miraftab, Faranak
ABSTRACT: This paper is in conversation with two important bodies of literature: one on informal settlements (informal and insurgent grassroots practices) and another on camps (spatial practices and governance of refugees). Reading inhabitants' experiences in Korail, an informal settlement in Dhaka, Bangladesh, through the literature grounded in the experiences of refugees, we seek to contribute to the relational theorization of informal settlements and camps as an expanding and overlapping reality in the era of intensified global displacements. Weaving back and forth between the camp literature and Korail's reality, we bring to light the comparable spatial practices and governance of the so-called citizens and the so-called stateless. We present the insights we gain from this analytical conversation under three organizing themes: experiential to highlight the precarious relationship of the two groups to citizenship and place, what we call a state of "citizenship in wait" and "in-situ displacement"; institutional to highlight the humanitarian matrices of care that provide governmental structures in both contexts; and micropolitical, to characterize dwellers' contestations with state and humanitarian governance that constitute the processes of life-making in informal settlements, much as in the camps. Conceptually the paper lends a forceful voice to the mounting critiques of the state-centered canon in planning theories and the needed Southern turn in planning theorization. Politically, it lends a hand to the efforts of activists working to overcome exclusions and erasures that are endemic to the politics of citizenship, that pit refugees against the poor, and to gesture toward forging solidarities for a humane urbanism.